Evaluations of the mutagenicity of a pigment extract from bulb culture of Hippeastrum reticulatum - Nitteranon, Viriya; Kittiwongwattana, Chockchai; Vuttipongchaikij, Supachai; Sakulkoo, Jenjira; Srijakkoat, Monthira; Chokratin, Pakawieng; Harinasut, Poontariga; Suputtitada, Saowanee; Apisitwanich, Somsak (My University, 2014)
The use of anthocyanins in food products as colorants has been limited because of their instability toward alkaline pH and high temperature. This study aimed to determine color stability and mutagenicity of the anthocyanin-based pigment extract from bulb cultures of Hippeastrum (Hippeastrum reticulatum). The pigment extract retained its reddish-orange color under alkaline conditions (≤pH 11) and was stable up to 6h at 95°C. The mutagenicity of the extract was evaluated in vitro and in vivo. Hippeastrum pigment extract up to 1.25mgplate-1 was found non-mutagenic in Ames test using Salmonella typhimurium strain TA98 and TA100. Chromosome aberrations were observed when human lymphocytes were treated with the extract up to 1.5mgml-1. However, the extract up to 1.4mgml-1 was found to exhibit relatively low or no mutagenicity in in vitro comet assays with human lymphocytes. In in vivo micronucleated reticulocyte assay, mice were treated orally with the extract up to 1gkg-1. No significant increase of the percentage of micronucleated peripheral reticulocytes compared to the negative control groups was found. Taken together, our study indicates that Hippeastrum pigment extract is potentially applicable as an additive colorant in the diet and related products. © 2014 Elsevier Ltd.
Keywords: Anthocyanin; Heat stability; Hippeastrum reticulatum; Mutagenicity; PH stability; Tissue culture